The clothing attitude of selected teenage girls in single mother family set-up - Gamutan, Maxine Ivana A.
ABSTRACT This is a descriptive research that aimed to examine the clothing attitudes of selected teenage daughters in single mother family set- up based on the implications of paternal absenteeism and maternal influence. The research also aimed to understand the significance of the circumstances of father absence and its relation to the clothing attitude of teenage girls. The scope of this study was limited to single mother family arrangements with an absent father due to out of wedlock birth, death, separation, or abandonment. The respondents were purposively selected with respect to gender (female), age (13 to 19 years old) and socio- economic status (middle class). There were 60 respondents in total. Online opinionnaire was the method of data collection. Data was tabulated by age when they lost their fathers and the manner they lost them. The Chi Square (X2) Contingency Test was utilized to determine whether these characteristics have significant implications on the clothing attitude of the respondents. Results indicate that what contributes much to their clothing attitude is paternal absenteeism. Without the father, there is no male confirmation on the way the daughter looks or dresses which results to insecurity and doubt about her ability to attract men. Because of that, the daughters have the tendency to try so hard to look good. Furthermore, the age when they lost their father has more influence on the clothing attitude of teenage daughters than the way these girls have lost their fathers. The daughters who have lost their fathers early in their childhood do not have that much issue regarding their clothing ways compared to the daughters who have lost their fathers during adolescence. The researcher recommends that further studies be made to validate the results of this study using a larger sample and that follow up studies be made to track the changes of the clothing attitude of teenage girls under single mother family set- up over time.